Olaparib induced aplastic anemia in a patient with castrate resistant prostate cancer: A case report - Elrazi A Ali; Monika Jain; Akriti Pokhrel; Unni Mooppan; Jen chin Wang (Leukemia Research Reports, 2024)
Olaparib is (ADP‐ribose) polymerase inhibitor (PARPi), which stops the repair of single-stranded DNA breaks. This leads to the death of cancer cells with BRCA1/BRCA2 mutations or homologous recombination deficiency. Since being approved by the FDA in 2023 for treating castrate-resistant prostate cancer (CRPC), there have been some reports of myelodysplastic syndrome (MDS) and acute leukemia linked to PARP inhibitor use for ovarian, breast, pancreatic and breast cancers, there have been no reports of aplastic anemia after receiving PARPi therapy. This case report describes a 75-year-old man with BRCA2-positive metastatic castrate-resistant prostate cancer who developed aplastic anemia after taking olaparib.